Factors and scenarios affecting a farmer's grain harvest logistics. (4th December 2019) - Kingwell, Ross; Loxton, Ryan; Mardaneh, Elham
Abstract : This paper explores how changes in Australia's grain industry supply chains are likely to impact on the nature and profitability of an Australian farmer's grain harvest logistics. A simulation model is used to show how receival site rationalisation, cheaper on‐farm storage, larger trucks, higher‐yielding crops and new harvest technologies, separately and in combination, affect the nature and profitability of a farmer's grain harvest logistics. Applying the model to a typical Australian grain farm shows that many of these changes unambiguously advantage the farm business, and often, the combination of these changes increases a farmer's harvest profits by at least 10 per cent. For many farmers, the task of efficiently designing and managing harvest logistics will be an increasingly difficult yet important series of choices due to the range of storage options, grain pathways, crop portfolios and market opportunities that are arising. A farmer's decisions about cost‐effective on‐farm storage and transport, and their judicious use, will be a key contributor to additional profit in future years.